Adolescent’s Mental Emotional - Malfasari, Eka; Sarimah, Sarimah; Febtrina, Rizka; Herniyanti, Rina (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
The phenomenon that occurs in adolescents is about the use of coping mechanisms that affect mental emotional conditions, due to the many behavioral deviations that occur in adolescents such as saying harshly to the teacher even to hitting the teacher and fighting between groups which is one of the emotional mental disorders. The purpose of this study was to determine the mental emotional state of adolescents in SMP Pekanbaru. This type of research is quantitative using descriptive design. The samples in this study were 216 people with stratified random sampling technique. The measuring instrument used was the Strenght And Difficulties Questionnaire (SDQ) Questionnaire to measure mental emotional states. This study uses univariate analysis. Adolescent mental emotional conditions as many as 78 people (36.1%) adolescents experience mental emotional conditions abnormal category, as many as 76 people (35.2%) adolescents with mental emotional conditions are normal categories, and as many as 62 people (28.7%) adolescents experience mental emotional state of the borderline category.